Efektivitas Program Ketahanan Pangan Di Gampong Keuramat Kota Banda Aceh - mukhrijal, mukhrijal; Wangsa Sunarso, Haikal; Hasanul Ichsan, Muhammad; Asrian, M. Fajar; Maulana, M. Ilham; Parawangsa, Mhd. Gibran (Program Studi Ilmu Politik, Universitas Syiah Kuala, Banda Aceh, 2023)
AbstractFood security is the ability of a region or country to meet the food needs of the entire population in a long term, both in sufficient quantity, safe, nutritious and affordable. This research was conducted in Gampong Keuramat which aims to determine the effectiveness of the Food Security Program in Gampong Keuramat. The method used by the authors in this study is a qualitative method. And also the approach used in this study is a library study approach, namely collecting library data through reading, taking notes, and reviewing several sources of information, books or texts used as references and references in research. The Food Security Program is expected to be able to realize that a country or region can independently meet its needs so that it does not depend on imports from othercountries.Keywords: Food Security; Gampong Keuramat; Effectiveness.